DETERMINATION OF SUNSET YELLOW AS A SYNTHETIC FOOD COLORANT IN CONFECTIONERY PRODUCTS CONSUMED IN KATSINA METROPOLIS (NIGERIA) USING UV-VIS SPECTROPHOTOMETER (FUDMA JOURNAL OF SCIENCES, 2021)
The use of Sunset yellow as food colorants in non-alcoholic drinks, beverages and confectionery is rising despite their problems upon consumption by humans. It is therefore, necessary to constantly monitor the concentrations of these dyes in our foods, beverages and confectionery because of their health-related issues that include hyperactivity in children and immune system compromise. For these reasons, the concentration of sunset yellow used as colorants was determined in ten different brands of confectionaries using the spectrophotometric method of analysis. A cross-sectional primary data was obtained through experimental procedures in ten different samples of confectionary products procured (Central Market Katsina, Nigeria). The results shown that the concentration for the two samples; E and I are 52.311Â±0.178 mg/L and 87.887Â±0.018 mg/L respectively were found to be above the acceptable permissible limit of 50mg/L, while for the remaining eight samples; A, B, C, D, F, G, H, and  J are, 46.523Â±0.116 mg/L, 49.364Â±0.418 mg/L, 41.924Â±0.029 mg/L, 27.853Â±0.029 mg/L, 33.045Â±0.018 mg/L, 29.515Â±0.028 mg/L, 34.250Â±0.019 mg/L and 33.295Â±0.018 mg/L respectively are within the acceptable permissible limit of 50 mg/L in accordance to Regulation (EC) No. 1333/2008 of the European Parliament and council establishing a Union list of food additives. Therefore, the results justify the safe consumption of samples A, B, C, D, F, G, H and J but samples E and I are not safe for consumption due to their concentration levels found above 50 mg/L.
Keywords: Sunset yellow, Food safety, Confectionaries, UV-Visible Spectrophotometer